Efeito do 1,3/1,6 beta-glucano no sistema imune de cadelas submetidas a ovário-histerectomia - Zaine, Leandro [UNESP] (2014)
Studies evaluating the effects of beta-glucans on the immune response have been made long ago; because of the immunemodulation that they cause can lead to increase resistance to infections and even to tumors. Thus, we conducted two experiments to evaluate the action of a yeast-derived beta-glucan in dogs. In the experiment 1 the ex vivo action was studied, canine leukocytes were treated with 3 different doses of beta-glucan and the results showed that the production of oxygen and nitrogen reactive species by neutrophils and monocytes was stimulated in a dose-dependent manner. In the experiment 2 the action of beta-glucan on immune parameters of bitches undergoing ovary-hysterectomy was evaluated, as a situation of immunosuppression. Twenty-eight bitches of different breeds were divided into three groups: control (CT – n=10), 0.1% beta-glucan in the extruded diet (BG-E – n=9) and supplemented with the same dose, but administered in capsules (BG-C – n=9). Evaluations were performed in four periods, 14 days before the surgery, immediate preoperative and postoperative and 14 days after the surgery. The tests performed included complete blood count, evaluation of leukocyte subsets, phagocytosis test, production of cytokines in supernatant of cell culture, production of oxygen and nitrogen reactive species and serum C-reactive protein. BG-C treatment lead to higher percentage of phagocytosis by monocytes. Only the control group tended to increase the concentration of C-reactive protein after the surgery. Surgical procedure was capable of changing the number of cells and their function. In conclusion, beta-glucan acted on the immunity considering the presented models